KEMAMPUAN MENGARANG DESKRIPSI BERDASARKAN OBSERVASI PADA SISWA KELAS V SDN 1 GULAK GALIK BANDAR LAMPUNG - Rahmasisca, Frieska Maryova (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2020)
The problem discussed in this study is the ability to write descriptions of Class V Odd Semester students of SD Negeri 1 Gulak Galik Bandar Lampung. The aspects studied include the suitability of the content of the essay, use of spelling, choice of words (diction), form of writing, and effectiveness of sentences. This research was conducted to determine the ability to compose descriptions and to determine the obstacles and factors of difficulty faced by students. The research method used is descriptive qualitative method. The research sample of 30 students was taken using a stratified proportional random sampling technique from the existing population. The data collection technique was carried out by means of a performance test, namely assigning students to make essays of descriptions based on objects in the school environment. Data analysis used quantitative analysis using a simple percentage formula. The results showed that the ability to write descriptions of class V Odd Semester SD Negeri 1 Gulak Galik Bandar Lampung was categorized as sufficient because the final score reached 67.The ability to compose descriptions was assessed from the aspect of the suitability of the contents of the essay, the ability of the students to reach an average score of 87.5 which was categorized as sufficient. , the spelling writing aspect reached an average score of 62 including the sufficient category, the word selection or diction aspect reached an average score of 50 including the poor category, the writing aspect of the student's ability reached an average score of 66 including the poor category, and the sentence effectiveness aspect of the students' ability achieving an average score of 68 is in the enough category. The aspect of suitability of the content of the essay became the highest mastery because the average obtained was 87.5, while the most difficult aspect was the choice of words or diction because the average score only reached 50, which was in the poor category.